2009
DOI: 10.1539/joh.l8158
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Serum γ‐glutamyltransferase Level as Risk Factors for Injuries Related to Professional Horse Racing: A Prospective Study

Abstract: Prevention of horse-related injuries is considered difficult because horse behavior is unpredictable. Therefore, risk factors for injuries related to professional horse racing need to be investigated. We conducted a study to determine w h e t h e r b o d y m a s s i n d e x ( B M I ) a n d γ -glutamyltransferase (GGT) levels are associated with professional horse racing-related injuries. Methods: A baseline healthy survey of 546 male grooms and exercise riders aged 40-70 yr working at Miho Training Center, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…A similar pattern and interpretation has been reported before [30]. For non-alcoholic liver pathology, c-GT obviously would be expected to better capture extent of liver damage and thus to be more predictive than alcohol consumption, even though the latter would be assumed to exacerbate the course of disease.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A similar pattern and interpretation has been reported before [30]. For non-alcoholic liver pathology, c-GT obviously would be expected to better capture extent of liver damage and thus to be more predictive than alcohol consumption, even though the latter would be assumed to exacerbate the course of disease.…”
Section: Discussionsupporting
confidence: 64%
“…In the general population, no association with death from respiratory causes or injury/poisoning was found in one large study [32], whereas c-GT may predict the risk of injuries in specific occupational settings [30]. We cannot fully explain the association with respiratory disease for the time being.…”
Section: Discussionmentioning
confidence: 83%
“…The physiological attributes of grooms and exercise riders,9 and the physiological demands of riding for equestrian and recreational horse riders2 10–14 have also been described. There is limited information on the fitness of jockeys, however, and no study has reported the fitness characteristics of track-work riders despite their integral role within the racing industry.…”
Section: Introductionmentioning
confidence: 99%
“…A cohort study of 546 male professional horse racing employees in Japan utilized injury data for those who applied for workers' compensation benefits showed a statistical signficance associated with BMI and increased risk for occupational injuries among professional horse racing employees. The highest overall injury rate was that of falls (out of 100 reported occupational injuries 32 cases were fall related) [19]. Based on a study of 101,891 U.S. adults from data derived from the National Health Interview Survey [20], of the 723 employees who experienced an occupational injury, approximately 21% were fall injuries associated with employee's being either overweight or obese [20].…”
Section: Slips Trips and Fall-related Injuriesmentioning
confidence: 99%
“…Another study of Canadian workforce (7,678 adults) using self-reported weight and height on National Population Health Survey (NPHS) found that obese workers experience up to a 49% higher risk of occupational injury and showed a pronounced association for injuries to the lower limbs for those workers who were overweight (OR = 1.03, 95% CI: 0.50 to 2.11) and those who were obese (OR = 2.14, 95% CI: 1.12 to 4.11) [15]. Risk factors were examined for lower extremity injuries using workers' compensation insurance benefit data from a cohort of 546 male employees in the professional horse racing industry [19]. High BMI was associated with increased risk for occupational injuries among professional horse racing employees and that overweight or obesity was found to be associated with low back and lower extremity injuries, most likely due to the high load on musculoskeletal structures of the excess weight.…”
Section: Upper/lower Extremity Injuriesmentioning
confidence: 99%